Assessment of properties of ultra-high performance cementitious composites with glass powder waste - Silvete Mari Soares; Taís Oliveira Gonçalves Freitas; Adalberto Oliveira Júnior; Fernanda Giannotti da Silva Ferreira; José Américo Alves Salvador Filho (Revista IBRACON de Estruturas e Materiais, 2022)
Abstract Novel developments on concrete technology such as high and ultra-high-performance concrete (HPC and UHPC) are notorious by its high consumption of Portland cement. Supplementary cementitious materials have been used as partial replacement of Portland cement aiming to minimizing clinker content, optimizing the use of binders, reducing CO2 emissions, and increasing durability. Waste glass powder could be an alternative due to its silica-rich nature and wide availability. This work aims to assess the influence Portland cement substitution by finely ground waste glass powder in contents of 10%, 20%, 30% and 50% on physical and mechanical behavior of ultra-high-performance cementitious composites (UHPCC). Results indicates the use of glass powder as substitution up to 50% of Portland cement does not significantly affect the analyzed properties at 28 days.